Enhancing biodiversity and production through participatory plant breeding: Setting breeding goals - Sthapit, B.R.; Joshi, Krishna D.; Rana, Ram B.; Upadhaya, Madhusudan; Eyzaguirre, Pablo B.; Jarvis, Devra I. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Participatory plant breeding (PPB) is one of the on-farm conservation strategies designed to maintain or enhance the level of landrace genetic diversity deployed on-farm. The global in situ project .aims to strengthen the skiIls and knowledge of local communities in locating and understanding the value of landraces, and also monitoring genetic erosion. Participation by famers and informal sectors in decentralized testing of materials can result in much greater diversity in the fields of collaborating fanners, as well as providing a broader range of varietal choices and adoption. Germplasm exchange between farmers and farmers' selection criteria can also contribute to and enhance on-farm conservation .and biodiversity. Within the project, "Strengthening the Scientific Basis of in situ Conservation of Agricultural Biodiversity," supported by the International Plant Genetic Resources Institute (IPGRI), case studies of rice were mode in Nepal on consolidating the roles of farmer participation in PPB .and seed exchange processes. Participatory methods, such as diversity fairs, diversity blocks, and community biodiversity registers, were used to understand the value of local diversity and .also to strengthen the roles of fanners and informal sectors in the local crop-development process. PPB programs in Nepal are designed to investigate (1) whether farmers' cultivars per se can be conserved, (2) if PPB has contributed to the enhancement of biodiversity in terms of a broader genetic base that provides benefits to the community, and (3) if genetic improvement was been achieved without loss of genetic diversity. This paper describes preliminary results of understanding genetic divergence in terms of the use value of local biodiversity and the participatory methods used to select landrace parents. Methodological constraints of participatory approaches in setting breeding goal. in the context of biodiversity enhancement and production objectives in biodiversity rich areas are discussed, The paper also documents how the needs of farmers and objectives of biodiversity enhancement can be integrated during the setting of breeding goals and supplying useful genetic diversity by bringing new, restoring old, and generating new genetic diversity (local x exotic) in the agro ecosystem in three eco-sites of Nepal.